Gorilla biology : a multidisciplinary perspective - Taylor, Andrea B. (Andrea Beth), 1961-; Goldsmith, Michele L. (Michele Lynn), 1963- (Cambridge studies in biological and evolutionary anthropology ;, 2003)
Gorillas are one of our closest living relatives, are the largest living primate, yet are perhaps the most misunderstood great ape. Teetering on the brink of extinction, they are also of increasing conservation concern. Gorilla Biology is the first comparative perspective on gorilla populations throughout their range.